Accounting Students’ perceptions of Social Responsibility Importance: Empirical Evidence from Saudi Arabia - EBEID, Ebrahem El Said (Journal of Finance & Corporate Governance, 2020)
This study aims to test the perception of accounting departments' students in Saudi universities as potential future financial managers in Saudi corporations of the importance of corporate social responsibility as one of the important factors in achieving the sustainable success and growth of these corporations. The researcher has relied on the descriptive analytical approach. By testing a sample of 94 students of accounting departments in Saudi universities, the study found that there was a weakness in these students' perceptions of the importance of corporate social responsibility. Students are more interested in maximizing value for shareholders through increasing profits and market value than interest in maximizing value for stakeholders in the community in which the company operates. This can explain the very weak disclosure of social responsibility in the published financial reports of Saudi corporation due to the weak culture of social responsibility of most managers in these corporations